From Pariah to Partner: The Effect of Translanguaging on The Strategic Competence of ESL Learners in Pakistan - Aftab Hussain; Shahabullah; Zakir Ali; Shan Zeb (University of Chitral Journal of Linguistics and Literature)
This study explores the impact of a translanguaging pedagogical approach on the development of strategic competence in English as a Second Language (ESL) learners focusing on secondary school students in Swabi, Khyber Pakhtunkhwa, Pakistan. Strategic competence, essential for managing communication breakdowns, remains underdeveloped in traditional monolingual ESL classrooms. This research used a quasi-experimental, pretest-posttest control group design with 10th-grade male students, comparing a translanguaging-based approach with a conventional monolingual teaching model. The experimental group used their first language (L1) as a cognitive resource in language learning, while the control group adhered to a traditional approach. The findings indicate a significant improvement in the strategic competence of the experimental group, suggesting that integrating L1 in ESL pedagogy enhances communication strategies and reduces affective filters. The study calls for a shift from monolingual to multilingual teaching practices in Pakistan's ESL classrooms, advocating for the use of students' full linguistic repertoire as an asset for language learning. The findings offer insights for curriculum developers, educators, and policymakers to improve ESL education in multilingual contexts.